2021
DOI: 10.3390/ijgi10110742
|View full text |Cite
|
Sign up to set email alerts
|

Moving Object Detection in Traffic Surveillance Video: New MOD-AT Method Based on Adaptive Threshold

Abstract: Previous research on moving object detection in traffic surveillance video has mostly adopted a single threshold to eliminate the noise caused by external environmental interference, resulting in low accuracy and low efficiency of moving object detection. Therefore, we propose a moving object detection method that considers the difference of image spatial threshold, i.e., a moving object detection method using adaptive threshold (MOD-AT for short). In particular, based on the homograph method, we first establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The results showed that IoT-based technology and modified techniques for taking out the background worked well together. By applying GMM Filter [22,23] to reduce unwanted small items, this research completes and continues object detection on video.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results showed that IoT-based technology and modified techniques for taking out the background worked well together. By applying GMM Filter [22,23] to reduce unwanted small items, this research completes and continues object detection on video.…”
Section: Introductionmentioning
confidence: 86%
“…Figure 2: Proposed ModelGaussian Mixture Model (GMM) is one of the ways to get rid of the background. GMM models the time series of pixel values[23][24][25]. The accuracy of the Gaussian Mixture Models (GMM) method in separating the background and the tracked object can be evaluated using several metrics, such as: a. Intersection over Union (IoU): This metric measures the overlap between the predicted object bounding box and the ground truth bounding box, divided by their union.…”
mentioning
confidence: 99%
“…The image size of motion detection can vary due to the effects of camera imaging characteristics, and the noise can easily influence the findings of motion detection. Because of this, the precision of the identification of moving objects is easily compromised [27], [28]. The presence of noise in an image will not only have an impact on how the image appears to the human eye, but it will also have an impact on the following processing of the image, such as the extraction of image features, the categorization, and recognition of images, and so on.…”
Section: Image or Video Noisementioning
confidence: 99%
“…Luo et al [27] used a method for detecting motion that considers the variation in the spatial image threshold. The researcher calculates the projected size of motion in the image regions by establishing the mapping relationship between the geometric features of motion in the image regions and the reasonable level circumscribed rectangle (BLOB) of motion in the geographic space.…”
Section: Image or Video Noisementioning
confidence: 99%